2016
DOI: 10.1007/s13224-016-0843-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Leptin Level in Women with Unexplained Infertility and Fertile Women in Iran

Abstract: Background Various studies have been conducted on the role of leptin in the different types of infertility, including endometriosis, polycystic ovaries and male infertility; however, only a few studies have been conducted on the effect of leptin on unexplained infertility. The purpose of the present study was therefore to compare serum leptin levels in women with unexplained infertility and fertile women as a contributing factor to female infertility in Iran.Methods The present case-control study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
(14 reference statements)
3
5
1
Order By: Relevance
“…Our results showed no significant difference in serum leptin level in the fertile and infertile groups. In contrast to our results, few studies have reported higher leptin levels in infertile male patients (Farooq, Lutfullah, & Ahmed, ; Jahan, Bibi, Ahmed, & Kafeel, ) while few other studies demonstrated results similar to our study (Dayer, Nikbakht, & Elyaderani, ; Tafvizi & Masomi, ). The inconsistency of results could be due to the difference in sample size, the use of different kits and variation in the dietary customs and lifestyles of different nations (Tafvizi & Masomi, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed no significant difference in serum leptin level in the fertile and infertile groups. In contrast to our results, few studies have reported higher leptin levels in infertile male patients (Farooq, Lutfullah, & Ahmed, ; Jahan, Bibi, Ahmed, & Kafeel, ) while few other studies demonstrated results similar to our study (Dayer, Nikbakht, & Elyaderani, ; Tafvizi & Masomi, ). The inconsistency of results could be due to the difference in sample size, the use of different kits and variation in the dietary customs and lifestyles of different nations (Tafvizi & Masomi, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the high leptin serum level was strongly associated with the low level of FSH and LH (negative association) and the high level of LH/FSH ratio and PRL in UI women (positive association). These findings are consistent with the previous findings from Turkey[ 29 ], Iraq[ 32 , 37 ] and Iran[ 31 ]. However, the reported change in these biomarkers (high PRL, low LH and FSH) can be related to female infertility due to the fact that low FSH and LH levels together with the high level of PRL in females can induce ovulatory dysfunction, implantation defects and abnormal ovarian steroidogenesis[ 13 , 38 ].…”
Section: Discussionsupporting
confidence: 94%
“…The current study revealed that the leptin serum level was significantly higher in women with UI compared with fertile women, 30.05 (95%CI: 29.34-30.76) and 22.89 (95%CI: 21.96-23.81), respectively, with a very large effect size of 1.225. This result is in line with the findings reported from Turkey[ 29 ], India[ 30 ], Iran[ 31 ] and Iraq[ 32 , 37 ], and in contrast with findings reported from Pakistan[ 33 ] and Iran[ 34 ]. The difference between the current findings reported from Sudan and other findings reported from other countries (which all were non-African countries), could be due to the difference in genetic makeup, sample sizes, age and BMI.…”
Section: Discussionsupporting
confidence: 92%
“…Kisspeptin receptor gene expression has been present in both the ARC (arcuate nucleus) and AVPV (anteroventral periventricular nucleus) of the hypothalamus. Kisspeptin secreted from hypothalamus causes a chain reaction which leads to the release of neurotransmitters from the pituitary gland (Terasawa et al, 2013).…”
Section: Leptin and Its Role In Pubertymentioning
confidence: 99%
“…The pattern of circulating leptin concentration various during pregnancy, high level of leptin was observed in mid-gestation and it decreases subsequently in postpartum as shown in figure 4. In humans, the maternal circulation facing syncytiotrophoblast and fetal circulation facing villous vascular endothelial cells were detected with placental leptin mRNA and a protein indicating the role of the placenta in the hyperleptinemia (Tafvizi and Masomi, 2016). The soluble isoform of leptin receptor (Ob-Re) expressed by human placenta reaches circulation by various ways and binds to the free leptin and thereby maintains high leptin levels in the plasma also this prevents the binding of free leptin to the other isomer of leptin receptor Ob-Rb (Anum et al, 2015).…”
Section: Effect Of Leptin In Female Reproductive Healthmentioning
confidence: 99%